Leader of the 'Free World'? Studying German Foreign Policy by Means of External Attributions. Issue 1 (2nd January 2021) - Franke, Ulrich
Abstract : Germany's position in global politics has been a vibrant topic in recent years – among politicians, academics, and in the media. After Donald Trump was elected US President, for instance, some commentators declared that the fate of the West was now in the hands of the German Chancellor Angela Merkel. Less than five years earlier, however, Merkel had been accused by some of the same commentators of disrupting the European Union in the sovereign debt and Euro crisis. Hence, this article traces the changing characterization of Germany across newspapers from the US, Britain, and Israel. Using the so-called refugee crisis, Britain's decision to leave the European Union and Trump's election as nodal points of the analysis, this article asks: what do we learn about Germany and the course of its foreign policy from external attributions? It examines leading articles, comments, and op-eds, to strive for an empirically grounded account of how these external attributions figure in the picture of German foreign policy. Embedded in a pragmatist model of the social, the study assumes that external attributions contribute to and form part of the rules for action guiding German foreign policymakers.